A Nanofiber Mat With Dual Bioactive Components and a Biomimetic Matrix Structure for Improving Osteogenesis Effect - Han, Yadi; Shen, Xiaofeng; Chen, Sihao; Wang, Xiuhui; Du, Juan; Zhu, Tonghe (Frontiers in Chemistry, 2021)
The challenge of effectively regenerating bone tissue through tissue engineering technology is that most tissue engineering scaffolds cannot imitate the three-dimensional structure and function of the natural extracellular matrix. Herein, we have prepared the poly(L-lactic acid)–based dual bioactive component reinforced nanofiber mats which were named as poly(L-lactic acid)/bovine serum albumin/nanohydroxyapatite (PLLA/BSA/nHAp) with dual bioactive components by combining homogeneous blending and electrospinning technology. The results showed that these nanofiber mats had sufficient mechanical properties and a porous structure suitable for cell growth and migration. Furthermore, the results of cell experiments in vitro showed that PLLA/BSA/nHAp composite nanofiber mat could preferably stimulate the proliferation of mouse osteoblastic cells (MC3T3 cells) compared with pure PLLA nanofiber mats. Based on these results, the scaffolds developed in this study are considered to have a great potential to be adhibited as bone repair materials.